THE DESIGN OF HOT MIXTURE THIN SURFACING CONTAINING ASBUTON MODIFIED BITUMEN FOR HOT AND ARID REGION - Kabbash1, Omar Muhamed; Setyawan, Ary; Handayani, Dewi (Jurnal Teknik Sipil, 2014)
AbstractHot arid region is a region when it is characterized by a severe lack of available water and has a high temperature like Australia and Africa. In this condition, hot mix asphalt (HMA) thin surfacing is chosen for road preservation. This study is aimed to study about modified asbuton for hot mix asphalt by thin surfacing overlay.For bitumen modified, researcher used three types of asphalt (asphalt penetration 60/70, retona blend 55 and polymer SBS) specimen which be add with 5%, 5.5%, 6%, 6.5% and 7% for each sample with thickness of 30mm. Moreover, for the temperature test, it was tested at 20oC until 60oC. The test showed that polymer SBS can be used as a binder for alternative industrial asphalt in flexible pavement at hot and arid region. Polymer SBS is good material that has same sensitivity in the different temperature. Result of marshall test showed that Polymer SBS more stable than asphalt penetration 60/70 and retona blend 55. Polymer SBS also has the highest density. Retona blend 55 has the better result for the test average that was conducted in this study.Keyword: HMA, thin surfacing, asbuton, bitumen, hot and arid.